Structural-functional analysis in theoretical sociology : a methodological inquiry - Slabbert, F. van Zyl (Frederik van Zyl), 1940-2010 (Stellenbosch : University of Stellenbosch, 2011)
Thesis (DPhil) (Sociology and Social Anthropology))--University of Stellenbosch, 1967.